Designing a Video Script of Travelin Application at PT Angkasa Pura II Palembang - Febriani, Weny; Gustiani, Sri; Ridhwan, Moehamad (Politeknik Negeri Sriwijaya, 2024)
This study aims to design a video script for the Travelin application at PT. Angkasa Pura II Palembang to facilitate customers' digital check-in and assist support officers. Employing a Research and Development (R&D) approach adapted from Plomp (1997) and utilising a qualitative descriptive design, the script design process included five stages: (1) preliminary investigation, (2) design, (3) realisation/development, (4) testing, evaluation, and revision, and (5) implementation. Data collection techniques comprised literature reviews and interviews, with thematic analysis applied to the interview data. Three experts, selected purposely—a scriptwriting expert, an Indonesian language expert, and an English language expert—participated in the script revision. Key findings from experts’ feedback highlighted the need to simplify sentences, enhance content engagement, incorporate contemporary language, and avoid redundancy. Language-specific suggestions included refining diction, addressing Indonesian affixes (e.g., di-), italicising English terms, and converting complex sentences to simpler structures. This refined script is anticipated to enhance the effectiveness of the Travelin application video at PT. Angkasa Pura II Palembang offers clear guidance to customers and improves digital security check-in processes.